(3JPjjd hJcejd (B( (3cJGH (B) (3GdLGeY GddWjas - (3CHh GdajV (B( (3hCHi GdESYGO (B) (3YHO GdSJGQ Hf YHO GdhgGH Hf NOGjGQ GdeHGQcTGghi GdHcQi GdUOjbi GdMfaj GdOgdhis; (3GHf XgjQI , eMeO Hf eMeO Hf CHj HcQ Hf Ydj Gdecj GdeNRhej, LeGd GdOjf,J (B986 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe Ydi ef TGA ef YHGOg HeLGhQI HjJg GdaNje CeG HYO , ajbhd GHh GdajV hCHh GdESYGO YHO GdSJGQ Efi bO TaYJ ef UZQ Sfi ai eWGdYI cJH GdJhGQjN hdGSjeG GdeJYdbI HCNHGQ ecI s
(3BNQgG (B:s
(3hde jRd GdTQja MSjf HGTG Hf Ydi ai EeGQI ecI eSJeQkG hHGbjkG Edi YGefG gPG , hgh GdYGe GdKGdK hGdKdGKhf hGdKdGK eFI hGdCda hgPG BNQ eG CQOJ JMQjQg hJfbjMg hJPjjd GdJGQjN GdePchQ Ydi hLg GdGNJUGQ GdMeO ddg s
(3ebGHdI heUMMIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs